Competitive marketing through Confucian values in Malaysia: a case study - Tossapon Luechapattanaporn (2018)
© 2016, © Emerald Group Publishing Limited. Purpose: The purpose of this paper is to stimulate debate about the advantages and disadvantages of incorporating Confucian values in personnel and marketing practices of a manufacturing firm in an ethnically diverse, emerging economy of Southeast Asia. Design/methodology/approach: Primary data from the direct experience of the company’s manager were combined with secondary sources of information on the business landscape of Malaysia. Key lessons were developed from discussion and reflection on experiences of people involved with the company. Findings: Cultivating warm, long-term relationships with customers through product dependability and gifts contributed to the firm’s marketing success. Family-like bonds between employees, “not strictly professional by Western standards” succeeded in keeping the turnover low. The paternalistic leadership style, however, came at the expense of a possible loss of constructive conflict through participatory decision-making. Research limitations/implications: Analysis is restricted to the experience of a single company. Research findings are thus highly context-specific. Originality/value: The case shows an example of successful implementation of key Confucian values in multiple business areas. The interplay between the East Asian values and the diverse ethnic context of Malaysia is also examined.